Barbara Lee : speaking truth to power [videorecording (DVD)] - Lee, Barbara, 1946-; Ocasio-Cortez, Alexandria, 1989-; Jones, Van, 1968-; Booker, Cory (Greenwich Entertainment, 2021)
With unique access to a sitting member of Congress, this documentary tells the complex story of Rep. Barbara Lee, a steadfast voice for human rights, peace, and economic and racial justice. She was the lone vote in opposition to the broad authorization of military force following the September eleventh attacks and is the highest-ranking African American woman in the United States Congress.